Evaluation of the condylar position in subjects with signs and symptoms of functional disorders of the temporomandibular joint through images made with cone beam computed tomography on the sagittal plane - Mazzetto, Marcelo Oliveira; Veneziam, Giovana Cherubini; Magri, Laís Valencise; Nasr, Mario Kaissar; Paiva, Alexandra Faria; Paiva, Guiovaldo (Brazilian Dental Science, 2014)
ABSTRACT: The aim of the study was to investigate the condylar position within the articular cavity in patients with temporomandibular disorders with signs and symptoms of functional articular disorders through images made with cone beam computed tomography (CBCT) on the sagittal plane. Methods: CBCT temporomandibular joints images of 62 patients (13 men and 49 women, average age, 39.7 years) with signs and symptoms intra-articular diagnosed by the Craniomandibular index were analyzed using the measurement method recommended by Kawamura and Ikeda (2009). We obtained the linear measures of posterior space (PS), superior space (SS), and the anterior space (AS) to determine the condyle position for each joint. Results: The average of the measurements of PS, SS, were respectively 1.9 mm (DP 0.5), 3.1 mm (DP 0.9), and 2.0 mm (DP 1.0). Conclusion: This study found that the subjects with intra-articular TMD when compared with the excellent condylar relationship established by Ikeda and Kawamura (2009) presented a more posterior and inferior condylar position.